The Influence of Leadership Style and Service Quality on Community Satisfaction - Fatmah Ma'ruf; Darman Darman; Marno Suleman; Lukman Setiawan (West Science Interdisciplinary Studies, 2024)
This research explains the influence of leadership style and service quality on community satisfaction, by observing 53 community samples. Data were analyzed using PLS-SEM techniques via SMARTPLS version 3 software. Samples were selected and collected through purposive sampling and distributed via online questionnaire via Google form. The results show that Leadership Style has an insignificant effect, with a TStatistic value of 1.461 and P Values of 0.145, while Service Quality has a significant effect, with a TStatistics value of 16.830 and P Values of 0.000 on Community Satisfaction.